Potential screening assays for individual radiation sensitivity and susceptibility and their current validation state. (3rd March 2020) - Gomolka, Maria; Blyth, Benjamin; Bourguignon, Michel; Badie, Christophe; Schmitz, Annette; Talbot, Christopher; Hoeschen, Christoph; Salomaa, Sisko
Abstract: Purpose: The workshop on 'Individual Radiosensitivity and Radiosusceptibility' organized by MELODI and CONCERT on Malta in 2018, evaluated the current state of assays to identify sensitive and susceptible subgroups. The authors provide an overview on potential screening assays detecting individuals showing moderate to severe early and late radiation reactions or are at increased risk to develop cancer upon radiation exposure. Conclusion: It is necessary to separate clearly between tissue reactions and stochastic effects such as cancer when comparing the existing literature to validate various test systems. Requirements for the assays are set up. The literature is reviewed for assays that are reliable and robust. Sensitivity and specificity of the assays are regarded and scrutinized for modifying factors. Accuracy of an assay system is required to be more than 90% to balance risks of adverse reactions against risk to fail to cure the cancer. No assay/biomarker is in routine use. Assays that have shown predictive potential for radiosensitivity include SNPs, the RILA assay, and the pATM assay. A tree of risk guideline for radiologists is provided to assist medical treatment decisions. Recommendations for effective research include the setup of common retrospective and prospective cohorts/biobanks to validate current and future tests.